Language Shaping Identity or Identity Shaping Language – a study on sensory sound-symbolism among native Macedonian speakers - Naumoska Sarakinska, Biljana; Ribarska, Emilija (The International Association for the Educational Role of Language, 2021)
A number of different theories exist concerning the origin of words. The aim of this paper is to provide an overview of the phýsis and the nómos/thesis theories about the origin of words, arguments debated even in one of Plato’s dialogues - Cratylus. It goes without saying that words show different relations between their form and their meaning. This paper takes a closer look at linguists’ divided opinions, presenting and comparing them, setting out from the notion that the forms of the words bear only an arbitrary association with their meaning, and goes on to discuss the notions of onomatopoeia, sound-symbolism and iconicity. Furthermore, this paper presents several studies covering the experimental approaches to sound-symbolism, with special attention devoted to sensory sound-symbolism. The summary of these studies suggests what potential elements of the form of the word might be responsible for the form meaning relationship in a word. In addition, a small-scale online survey was conducted with the aim to investigate potential sensory sound-symbolism in Macedonian based on the above-mentioned studies, in order to see what similarities and differences exist. Evidence of patterns of non-arbitrariness present in language is analyzed through a discussion of the relation between the form, particularly the sounds and the meaning of words.
Keywords: arbitrariness, sound-symbolism, iconicity, form-meaning relations, ideophones